IMPLEMENTASI METODE PROJECT BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII SMP 11 MA’ARIF BANGSALSARI - Ilyas, Muhammad; Rosyidah, Ulfatur (FAJAR Jurnal Pendidikan Islam, 2023)
This research is motivated by low student learning outcomes because most teachers teach using conventional teaching methods and lectures. The purpose of this study was to find out specifically how the application of the project based learning method in improving student learning outcomes in the subjects of Islamic Religious Education class VIII SMP 11 Ma'arif Bangsalsari and how to improve student learning outcomes through the application of the Project Based Learning method on the subjects of Religious Education. Islamic class VIII SMP 11 Ma'arif Bangsalsari. To answer the above question, the author uses a field research type and is descriptive qualitative, so the data from this study was obtained through observation, interviews, and documentation using triangulation of sources as an instrument to check the validity of the data. From the results of this study, it can be seen that the implementation of the Project Based Learning Method in improving student learning outcomes in Islamic Religious Education subjects for class VIII SMP 11 Ma'arif Bangsalsari is able to improve student learning outcomes in understanding the material like doing good deeds and being kind to all. It is proven by the existence of students who are starting to be active and learning outcomes increase.